Teachers’ visual processing of children’s off-task behaviors in class: A comparison between teachers and student teachers - Hirofumi Shinoda (Public Library of Science (PLoS), 2021)
As teachers are responsible for responding instantaneously to students’ statements and actions, the progress of the class, and their teaching purpose, they need to be able to engage in responsive teaching. Teachers obtain information about students’ learning by observing them in the classroom, and subsequently make instructional decisions based on this information. Teachers need to be sensitive to student behaviors and respond accordingly, because there are students who follow the teacher’s instructions and those who do not in every classroom. Skilled teachers may distribute their gaze over the entire class and discover off-task behaviors. So how does a teacher’s visual processing and noticing ability develop? It is important to clarify this process for both experienced teachers and student teachers. Therefore, the purpose of this study was to investigate whether there is a difference in visual processing and the ability to notice off-task behaviors in class between teachers and student teachers through gaze analysis. Using an eye tracking device, 76 teachers and 147 student teachers were asked to watch a video, and gaze measurements were collected. In the video, students exhibiting off-task behaviors in class were prompted by their classroom teacher to participate in the lesson. After the video, the participants were asked if they could identify the students who had displayed off-task behaviors and whom the teachers had warned. The results showed that teachers gazed at students engaging in off-task behaviors in class more often and noticed them at a higher rate than student teachers did. These results may be attributed to differences in the experiences of visual processing of relevant information in the classroom between teachers and student teachers. Thus, the findings on teachers’ visual processing by direct measurement of gaze will be able to contribute to teachers’ development.